Capacity building and consultation meeting on wildlife farming and zoonotic diseases management for stakeholders and value chain actors in Thai Nguyen, Vietnam - Nguyen Thi Thanh Ha; Lo Quang Thanh; Nguyen Thi Minh Phuong; Nguyen Thi Thu Hien; Thomas, Lian F.; Hung Nguyen-Viet; Phan Thi Hong Phuc; Pham Thi Trang; Sinh Dang-Xuan (International Livestock Research Institute, 2025)
On 17-18 December 2025, the International Livestock Research Institute, in collaboration with Thai Nguyen University of Agriculture and Forestry and the Sub-Department of Forestry Protection of Thai Nguyen Province, hosted a multi-stakeholder workshop on wildlife farming and zoonotic diseases management. The event brought together 36 participants from local authorities across agriculture, forestry, animal and human health, and environmental sectors, alongside research institutions, universities, rescue center and international organization, and actors along the wildlife value chains (wildlife farmers, traders, and processors). The workshop focused on (i) strengthening governance, management capacity, and coordination for zoonotic risk prevention in wildlife farming systems, and (ii) identifying priority wildlife value chains, zoonotic risks, and transmission pathways to inform future research and interventions.